Carbon Fiscal Instruments and Green Finance: An Aid to the Success of SDGs in Nigeria? - Onanuga Olaronke Toyin; Abayomi Toyin Onanuga (Journal of Innovation in Business and Economics, 2019)
The need to improve on the use of Fiscal Instruments and engender an improvement in Green Finance remains a challenge in Nigeria. Using the Metcalf’s Framework, this paper explains why Carbon Fiscal Instruments are enforced on emitters to check emissions and their level of effectiveness. Furthermore, a comparative analysis of Nigeria’s performance with some sub-Saharan African countries using the SDGs Index and Dashboard Indicators Framework was discussed. Finally, after appraising the use of Green Finance as a means of innovative finance, the paper found a dearth of fiscal instruments in Nigeria coupled with a low level of Green Finance opportunities. The paper concludes that Nigeria needs to design and implement an optimal climate change fiscal policy and Green Finance mix for Green growth. We recommend that the government needs to encourage creative and innovative ways of generating funds for Green investments in the private sector.